Structure-Based In Silico Investigation of Agonists for Proteins Involved in Breast Cancer. (6th January 2022) - Roy, Arpita; Anand, Ashutosh; Garg, Saksham; Khan, Mohd Shahnawaz; Bhasin, Sidharth; Asghar, Muhammad Nadeem; Emran, Talha Bin
Abstract : Cancer is recognized as one of the main causes of mortality worldwide by the World Health Organization. The high cost of currently available cancer therapy and certain limitations of current treatment make it necessary to search for novel, cost-effective, and efficient methods of cancer treatment. Therefore, in the current investigation, sixty-two compounds from five medicinal plants ( Tinospora cordifolia, Ocimum tenuiflorum, Podophyllum hexandrum, Andrographis paniculata, and Beta vulgaris ) and two proteins that are associated with breast cancer, i.e., HER4/ErbB4 kinase and ER α were selected. Selected compounds were screened using Lipinski's rule, which resulted in eighteen molecules being ruled out. The remaining forty-four compounds were then taken forward for docking studies followed by molecular dynamics studies of the best screened complexes. Results showed that isocolumbin, isopropylideneandrographolide, and 14-acetylandrographolide were potential lead compounds against the selected breast cancer receptors. Furthermore, in vitro studies are required to confirm the efficacy of the lead compounds.